Effect of 8-week multilateral training on physical and technical performance in young karateka - Greco, G. (European Journal of Physical Education and Sport Science, 2020)
Karate training, a Japanese martial art, is considered enough to increase physical-motor and technical performance. Instructors seem to prefer only technical Karate training to other physical-motor training methods. Therefore, the purpose of the present investigation was to assess the effects of 8 weeks of multilateral training on the physical-motor performance and technical gesture quality in young karateka. Participants (8-10 years) were recruited from a karate school and pair-matched based on gender and then randomly assigned to either an experimental group (EG, n = 14) or a control group (CG, n = 14). The EG was trained three times per week on non-consecutive days replacing a part of karate training with a multilateral training (i.e. flexibility, balance, strength and coordination, 45 min.) without increasing the total training time (90 min.). At baseline and after 8-weeks all participants were tested on the sit and reach, stork balance stand, standing long jump, and Harre test, and the technical gesture quality through the prefixed decision-making criteria. After intervention, the EG group showed significantly improvement than CG in the sit and reach test (2.0 vs. 1.1 cm, p < 0.001, ES = 0.73) and standing long jump test (8.3 vs. -4.0 cm, p < 0.01, ES = 0.88). Furthermore, the subjective evaluation scores of the technical gesture were significantly enhanced (p < 0.001, ES = 0.6 - 2.0) for EG in terms of technique, power, expressiveness and rhythm, whereas for CG the scores remained unchanged. Results suggested that incorporating a physical-motor training with a multilateral approach to karate technical sessions was more effective than technical training alone to improve physical-motor and technical performance in children.